Adaptation and Psychometric Properties of the Spanish Version of Child and Youth Resilience Measure (CYRM-32) - Llistosella, María; Gutiérrez-Rosado, Teresa; Rodríguez-Rey, Rocío; Liebenberg, Linda; Bejarano, Ángela; Gómez-Benito, Juana; Limonero, Joaquín T. (Frontiers in Psychology, 2019)
Resilience is defined as a dynamic process that entails a positive adaptation to contexts of adversity. According to the ecological model, resilient behavior emerges as a result of the interaction between individual, relational, community and cultural variables. The Child and Youth Resilience Measure (CYRM-28), developed in Canada and based on the ecological model, has been validated in several countries. The objective of this article is to present the cultural adaptation (studies I and II) and validation (study III) in Spanish at risk youth. A three-study mixed-method design was selected. Study I includes translations and a confirmatory and exploratory factor analysis of a sample of 270 Spanish young persons (56.9% boys) aged 12 -18 years (M=14.65; SD= 1.27) from an urban public elementary school. Study II uses semi-structured interviews with adolescents identified as resilient and presents a content analysis and a reformulation of items with experts. Study III includes the confirmatory factor analysis, internal consistency, test-retest, convergent and discriminant validity, and MANOVA to explore group differences of the resulting scale CYRM-32. The sample consisted of 432 at-risk young persons (54.9% boys and age M = 14.99; SD = 2.23). The results confirm the adequate psychometric properties of the CYRM-32 scale. From the original scale, 4 items were eliminated, 5 were reformulated presenting very low saturations. Meanwhile, 6 items were added to the cultural adaptation phase, resulting in a 32-item scale. The confirmatory analysis confirms the 3 factors expected in the CYRM-32 scale with good reliability indexes (Cronbach's alpha total scale .88, family interaction .79, interaction with others .72 and individual skills .78). The scale has convergent and discriminant validity in relation to the Brief Resilient Coping Scale, Coping Scale for Adolescents and Self-Concept. Significant differences were found in the scores of the CYRM-32 scale for the ethnic variable (F (71. 358) = 1.714, p <.001), while no differences appear according to age and gender. This finding confirms the importance of culture in the resiliency processes. The CYRM-32 scale has good psychometric properties and is a new alternative for measuring resilience in Spanish at-risk youth.